2008
DOI: 10.1017/s0007114508030808
|View full text |Cite
|
Sign up to set email alerts
|

Calcium plus vitamin D supplementation and fat mass loss in female very low-calcium consumers: potential link with a calcium-specific appetite control

Abstract: This randomized, double-blind, placebo-controlled study was conducted to compare the effect of a 15-week weight-reducing programme (2 2900 kJ/d) coupled with a calcium plus vitamin D (calciumþ D) supplementation (600 mg elemental calcium and 5 mg vitamin D, consumed twice a day) or with a placebo, on body fat and on spontaneous energy/macronutrient intake. Sixty-three overweight or obese women (mean age 43 years, mean BMI 32 kg/m 2 ) reporting a daily calcium intake , 800 mg participated in present study. Anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 20 publications
11
106
0
1
Order By: Relevance
“…In the study, ovariectomy resulted in a significant increase in body weight and also an increase in visceral fat, confirming previous findings [36,37], This indicates that the lack of estrogen following ovariectomy influences body weight, partially by increasing visceral fat [1,3]. Estrogen plays a crucial role in distributing visceral fat, probably by changing lipoprotein lipase activity [1,3,38]. Our study revealed that exercise training decreases body weight, which has also been reported in many studies [39,40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study, ovariectomy resulted in a significant increase in body weight and also an increase in visceral fat, confirming previous findings [36,37], This indicates that the lack of estrogen following ovariectomy influences body weight, partially by increasing visceral fat [1,3]. Estrogen plays a crucial role in distributing visceral fat, probably by changing lipoprotein lipase activity [1,3,38]. Our study revealed that exercise training decreases body weight, which has also been reported in many studies [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…If, yes, by what mechanisms could this interaction be explained? Recently, numerous interventional and epidemiological studies have shown that calcium and vitamin D consumption effectively reduce abdominal fat and metabolic syndrome risk [38,86]. It has been reported that vitamin D plays an essential role in the homeostasis control of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms by which Ca/dairy intake may play a role in regulating body weight are still unknown, but a number have been proposed: Impact of Ca on weight has been extensively studied (49 RCTs) and reviewed (Lanou & Barnard, 2008). One meta-analysis using 15 RCTs examining effect of Ca on fat excretion (Christensen et al, 2009).Two RCTs (Major et al, 2009;Major et al, 2008) examining effect of Ca on appetite with equivocal results. Only 4 RCTs show Ca contributes to greater weight loss with energy-restricted diet (~2-4 kg; Zemel, 2004Zemel, , 2005Zemel, , 2008.…”
Section: Calciummentioning
confidence: 99%
“…As a first attempt to test the validity of a calcium appetite in humans, obese individuals with very low calcium intake participated in a weight loss program with or without calcium plus vitamin D supplementation. The mean weight loss over 15 weeks was 5.8 and 1.4 kg in supplemented and placebo controls, respectively (Major et al 2009). The use of a buffet-type meal to measure ad libitum energy intake before and after the study revealed that most of the between-group difference in energy balance was explained by variations in energy/lipid intake.…”
Section: Micronutrients: a Potential Role In Satietymentioning
confidence: 98%